The communication disorders workbook - Cummings, Louise (Cambridge : Cambridge University Press, 2014)
Designed to help those studying speech-language pathology, this highly useful workbook is both an introduction to the basic concepts and a teaching tool to develop and test students' knowledge. Frequently encountered communication disorders are included, as are conditions less commonly found in speech-language pathology curricula but which feature increasingly in clinical caseloads. The book features: 330 short-answer questions help students to develop knowledge of the causes and features of communication disorders 60 data analysis exercises give students practice in analysing clinical linguistic data Full answers to the exercises are provided, saving the lecturer time in devising responses; students can use the responses to test their own knowledge and understanding A detailed glossary of terms makes the text self-contained, avoiding the need to consult other sources for explanations Suggestions for further reading are provided for each chapter.
Introduction to communication disorders -- Developmental speech disorders -- Developmental language disorders -- Communication disorders in mental illness -- Acquired speech disorders -- Acquired language disorders -- Disorders of voice -- Disorders of fluency -- Hearing disorders.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Communicative disorders; Language disorders